DISAIN KAPAL PENANGKAP IKAN 10 GT BERBAHAN FIBERGLASS UNTUK WILAYAH PERAIRAN KECAMATAN PANIMBANG KABUPATEN PANDEGLANG - Sudjasta, Bambang; Djaya, Yuhani (Bina Teknika, 2015)
The potential of Indonesian marine fisheries resources magnitude of ± 6.6 million tons / year, but only some can be captured by Indonesian fishermen is ± 4.7 million tons / year, partly stolen by fishermen from neighboring countries. This is due to the limited number and large size of fishing vessels operating.One of the areas that have the potential for capture fisheries is Panimbang Pandeglang District of Banten Province. Subdistrict of Panimbang the coastal region directly opposite the Sunda Strait. This region has a coastline and marine areas large enough.In order to improve the ability of the fishermen in the subdistrict Panimbang, it is necessary to build a fishing vessel that is suitable for this region. Where the design and construction of fishing vessel can be realized, then in turn the welfare of the fishermen in the region will increase.Fishing vessel designed the planned use of materials / raw materials fiberglass. This is because due to the high cost of steel plate material, problems also trouble getting wood materials. The fishing vessel design includes determining the size of the subject, the manufacturing line drawings, preparation of general plans, construction design, stability diagram, engine power and tonnage.